Numerical modelling and simulation of fatigue damage in carbon fibre reinforced plastics at different stress ratios. (June 2019) - Brod, M.; Just, G.; Dean, A.; Jansen, E.; Koch, I.; Rolfes, R.; Gude, M.
Abstract: A numerical study of damage behaviour in unidirectional Carbon Fibre Reinforced Plastics (CFRP) laminates at different stress ratios is self implemented. The study is conducted using the commercial finite element software ABAQUS employing a layer-based fatigue damage model (FDM) that is capable to regard typical fatigue phenomena like stress redistributions and load sequence effects. A description of the FDM model is provided. At first, the model is calibrated according to experimental findings. Next, a constant fatigue life (CFL) diagram is constructed using actual test data to generate S - N curves for different stress ratios. Finally, different damage behaviour in CFRP laminates is predicted under quasi-static and cyclic loading conditions. The numerical results are discussed and compared to experimental data. The results obtained show the applicability and accuracy of the calibrated FDM. Abstract : Highlights: An energy-based fatigue damage model was calibrated for carbon fibre reinforced plastics. The proposed method was employed in the commercial finite element software ABAQUS. The calibrated model was used for the damage prediction in CFRP laminates at different stress ratios. A comparison with experimental tests was conducted. The obtained results showed the applicability of the calibrated fatigue damage model.